Work status outcomes of vocational rehabilitation clients who are blind or visually impaired - Hill, M. Anne [Verfasser] (My University, 1989)
"Using data from the Rehabilitation Services Administration on 18.394 blind and visually impaired individuals who were successfully rehabilitated during fiscal 1982, the author estimated the effects of socioeconomic and VR program variables on the probability that a client will be (a) placed in the competitive labor market, (b) self- employed, (c) placed in sheltered work, or (d) established as a homemaker. Maximum likelihood estimation yielded empirical results that indicate that sex, age, race, marital status, the severity of the visual impairment, and the type of services provided significantly influence the employment outcomes of visually impaired men and women." (author's abstract) ((en)) Anhand der Daten von 18.394 Blinden und Sehbehinderten, deren Rehabilitation 1982 in den USA erfolgreich abgeschlossen wurde, schätzt der Autor die Wahrscheinlichkeit, dass ein Rehabilitand a) eine Arbeitstelle auf dem allgemeinen Arbeitsmarkt findet, b) selbständig tätig, c) in einer Behindertenwerkstätte oder d) im Haushalt beschäftigt sein wird. Die Ergebnisse der Maximum- Likelihood-Schätzung legen den Schluss nahe, dass das Geschlecht, das Alter, die Rasse, der Familienstand, die Schwere der Behinderung und die Ausstattung der Dienste den Beschäftigungsstatus rehablitierter Blinder und Sehbehinderter signifikant beeinflussen. (IAB)
Berufliche Rehabilitation und Stellung im Erwerbsleben von Blinden und Sehbehinderten
Keywords: G 1.3.3.4 Wiedereingliederung; G 2.3.1 Arbeitsteilung & -organisation; Menschen mit Behinderung; Blindheit; Sehbehinderung; Berufliche Rehabilitation; Erfolgskontrolle; Berufliche Integration; Einflussfaktor; Quantitative Angaben